The effects of inward FDI communities on the research and development intensity of emerging market locally domiciled firms : Partial foreign ownership as a contingency - Wu, Jie; Zahoor, Nadia; Khan, Zaheer; Meyer, Martin (Elsevier, 2022)
This study examined how inward foreign direct investment (IFDI) concentration affects the research and development (R&D) strategies of locally domiciled firms operating in emerging markets. From a resource dependence perspective, we argued that any community-specific interdependencies between local and foreign firms stimulate the former to engage in R&D activities. The findings of our analyses of panel data of 161,632 manufacturing firms across 525 four-digit-coded industries operating in China support our predictions that the R&D intensity of local firms responds positively to the presence of IFDI in competitive and symbiotic communities. In addition, the positive effects of IFDI on the level of R&D intensity of locally domiciled firms in competitive and symbiotic communities are enhanced by the foreign ownership of such firms. We conclude this paper by drawing the implications of our findings for theory and practice.
Keywords: Inward FDI; R&D intensity; Knowledge spillover; Interdependence between foreign and local firms; Resource dependence theory; Emerging market; emerging markets; foreign ownership